Impact of PET/CT on Staging and Treatment of Advanced Head and Neck Squamous Cell Carcinoma. (21st August 2018) - Jorgensen, Jeffery B.; Smith, Russell B.; Coughlin, Andrew; Spanos, William C.; Lohr, Michele M.; Sperry, Steven M.; Militsakh, Oleg; Zitsch, Robert P.; Yueh, Bevan; Dooley, Laura M.; Panwar, Aru; Galloway, Tabitha L. I.; et al.
Abstract : Objective: To understand the effects of positron emission tomography/computed tomography (PET/CT) evaluation on patients with previously untreated head and neck squamous cell carcinoma (HNSCC) with clinical evidence of regional lymph node involvement. Study Design: Prospective blinded study. Setting: Tertiary care cancer center. Subjects and Methods: Informed consent was obtained and data collected from 52 consecutive previously untreated patients with HNSCC and clinical evidence of cervical metastasis. All patients underwent conventional evaluation for HNSCC and whole body PET/CT. Data were evaluated by 5 independent reviewers, who performed TNM staging per the American Joint Committee on Cancer (seventh edition) manual and proposed a treatment plan prior to viewing, and after reviewing, PET/CT. Cases where at least 3 of 5 reviewers agreed were considered significant. Results: There were 0 patients for whom review of the PET/CT altered the T‐class assessment (95% CI, 0‐6.8), 12 (23.1%) for whom PET/CT altered N classification (95% CI, 12.5‐34.5), and 2 (3.8%) for whom PET/CT altered the M classification (95% CI, 0.5‐13.2). For 5 patients (9.6%), overall stage was altered per PET/CT review (95% CI, 3.2‐21). For 3 patients (5.8%), PET/CT findings prompted reviewers to alter treatment recommendations (95% CI, 1.2‐15.9). Conclusion: When added to more conventional patient evaluation, PET/CT results in changes to the TNM categories, but overall staging and treatment were less frequently affected. Whether PET/CT should be used routinely for patients with stage III and IV HNSCC is still subjective and merits further study.